2015
DOI: 10.1017/s0022029914000697
|View full text |Cite
|
Sign up to set email alerts
|

Mammary gland development of dairy heifers fed diets containing increasing levels of metabolisable protein: metabolisable energy

Abstract: This study was conducted to evaluate the development of the mammary gland in Holstein heifers subjected to different dietary metabolisable protein (MP): metabolisable energy (ME) ratios. Twenty-five Holstein heifers (initial body weight (BW) 213±13·5 kg and initial average age 7·8±0·5 months) were divided into five treatments. The treatments were designed to provide MP:ME ratios equal to 33, 38, 43, 48, and 53 g of MP per Mcal of ME. All diets were formulated to have the same energy content (2·6 Mcal ME/kg dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 27 publications
(33 reference statements)
1
52
1
Order By: Relevance
“…Heifers receiving the 50:50 (roughage:concentrate) treatment gained 0.70 kg d -1 . According to Albino et al (2015), it is not recommended for Holstein heifers to gain more than 1 kg d -1 in the rearing phase to avoid fat accumulation in the mammary gland; however, for crossbred heifers, the maximum gain has not yet been established. According to several authors, the average daily gain around 0.70 kg d -1 (Abeni et al, 2000;Shamay et al, 2005) is ideal to achieve target milk performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heifers receiving the 50:50 (roughage:concentrate) treatment gained 0.70 kg d -1 . According to Albino et al (2015), it is not recommended for Holstein heifers to gain more than 1 kg d -1 in the rearing phase to avoid fat accumulation in the mammary gland; however, for crossbred heifers, the maximum gain has not yet been established. According to several authors, the average daily gain around 0.70 kg d -1 (Abeni et al, 2000;Shamay et al, 2005) is ideal to achieve target milk performance.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, for Holstein heifers gaining more than 1 kg d -1 , it is not recommended (Albino et al, 2015); however, for crossbred heifers, the maximum gain has not yet been established. Thus, we hypothesized that the establishment of a proper roughage to concentrate ratio, using sugarcane bagasse as exclusive roughage for dairy heifers in the rearing phase could promote the anticipation of the first calving.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the heifer restrained in a standing position, the lubricated micro-convex transducer was applied to the base of each teat at a 45° angle, in a caudal-to-cranial placement ( Figure 1A). This procedure was obtained from Nishimura et al (2011) and adapted (Albino et al, 2015).…”
Section: Technical Notementioning
confidence: 99%
“…However, if heifers are simultaneously provided with an adequate level of protein this may minimize the adverse effects of feeding a high amount of energy. Recently, ALBINO et al (2015) reported that in prepuberal heifers fed to achieve an ADWG of 1000g, using a low dietary metabolisable protein: metabolizable energy ratio induced an excessive fat accumulation in the parenchymal area of mammary gland compared with higher ratios. This may explain why heifers can achieve higher ADWG than those recommended by ZANTON & HEINRICHS (2005) without having an impaired mammary development (SILVA et al, 2002).…”
Section: Introductionmentioning
confidence: 99%